PERSEPSI GURU HONORER SEKOTA PALEMBANG TERHADAP HAMBATAN DAN TANTANGAN DALAM MELAKSANAKAN TUGAS PENGAJARAN - Neta Dian Lestari (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
The problems in this study is "What is the perception of honorary teachers in Palembang City against the obstacles and challenges faced in carrying out their duties?". The purpose of this study, based on the formulation of a problems is to review the obstacles and challenges that occur or experienced teachers honorary in carrying out their duties. This research uses single variable that is Perception of Honorary Teachers of Palembang City against Barriers and Challenges in Running Teaching Task Year 2016/2017. The method used in this research is descriptive research method. This study was conducted Against 19 schools in the city of Palembang, for, get data about teachers honorary. the place. Research sample was taken to 28 teachers honorary. Data collection techniques used are documentation techniques and questionnaires. The honorary teacher is asked to fill out a questionnaire with 48 questions. It is concluded that of the six indicators of economic and accounting teaching preparation, economic and accounting teaching process, economic and accounting teaching and learning medium, economic and accounting teaching methods, economic and accounting teaching evaluation, and remedial economic teaching and accounting of honorary teachers in Palembang city percentage category No Difficulties (TK) 50.66% is the largest, 38.66% category Simply Difficulty (CK), Difficulty category (K) 9.58%, and the category Very Difficult (SK) 1.10%. It can be concluded that the honorary teachers in Palembang city in the average category do not experience difficulties with the percentage of 50.66%.